as-Indaceno[3,2,1,8,7,6-ghijklm]terrylene as a near-infrared absorbing C70-fragment - Yuki Tanaka (Nature Portfolio, 2020)
The synthesis of hydrocarbons with attractive electronic structures remains challenging. Here, the authors describe the synthesis and properties of the C70 fragment as-indaceno[3,2,1,8,7,6-ghijklm]terrylene, which exhibits near-infrared (NIR) absorption.